Special relativity : a heuristic approach - Hassani, Sadri (Elsevier, 2017)
This book provides a qualitative exposition of relativity theory on the basis of the constancy of the speed of light. Using Einstein's signal velocity as the defining idea for the notion of simultaneity and the fact that the speed of light is independent of the motion of its source, chapters delve into a qualitative exposition of the relativity of time and length, discuss the time dilation formula using the standard light clock, explore the Minkowski four-dimensional space-time distance based on how the time dilation formula is derived, and define the components of the two-dimensional space-time velocity, amongst other topics. It provides a heuristic derivation of the Minkowski distance formula, uses relativistic photography to see Lorentz transformation and vector algebra manipulation in action, and includes worked examples.